Conservation of the global sex determination gene tra-1 in distantly related nematodes - Pires-daSilva, André (Cold Spring Harbor Laboratory Press, 2004)
Sex determination has long intrigued evolutionists, geneticists, and developmental biologists in a similar way. Substantial evidence indicates that sex determination evolves rapidly and, therefore, can be used to study how molecular patterning processes evolve. In Caenorhabditis elegans, sex determination relies on a signaling pathway that involves a cascade of negatively acting factors, finally triggering the GLI-family zinc-finger transcription factor TRA-1. We have started to investigate sex determination in the nematode satellite species Pristionchus pacificus that is separated from C. elegans for 200–300 million years. In P. pacificus, animals with two X chromosomes develop as hermaphrodites, whereas XO animals develop as males. We used an unbiased forward genetic approach and isolated several mutants with a hermaphrodite to male transformation of the XX karyotype. We identified one complementation group as representing the P. pacificus ortholog of tra-1, providing the first evidence for the conservation of a global sex determination gene over a time period of at least 200 million years. A Ppa-tra-1 morpholino phenocopies Ppa-tra-1 mutants and establishes the morpholino technology as a reverse genetic approach in P. pacificus.